Epidemiology of Childhood Cancer in âDharmaisâ Cancer Hospital - mahdi, hardini intan s; rini, anky tri; tehuteru, edi setiawan (Indonesian Journal of Cancer, 2010)
Epidemiology of Childhood Cancer in âDharmaisâ Cancer HospitalÂ Full text : http://www.scribd.com/doc/43593777/Epidemiology-of-Childhood-Cancer-in-Dharmais-Cancer-Hospital